KEBIJAKAN DAN PENGEMBANGAN PENDIDIKAN SEKARANG DAN MASA DATANG1 - Baedhowi2 Baedhowi2 (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2019)
Education has undoubtedly become one of the most crucial pillars for enhancing thecountry’s competitive advantage. Well-designed education system will produce capable generations who proceed, even improve the performance of development programs. To meet such a circumstance, it is imperative for the government to formulate a range of relevant policy leading to the better education quality.